UN human rights treaty bodies : law and legitimacy - Keller, Helen , 1964-; Ulfstein, Geir , 1951- (Studies on human rights conventions, 2012)
"The effective implementation of human rights treaty obligations in national law is subject to increasing attention. The main responsibility for the international monitoring of national implementation at the global level is entrusted to the UN human rights treaty bodies. These bodies are established by the respective human rights conventions and are composed of independent experts. This book examines three aspects of these bodies: the legal aspects of their structure, functions and decisions; their effectiveness in ensuring respect for human rights obligations; and the legitimacy of these bodies and their decisions. Containing contributions from a variety of eminent legal experts, including present and former members of the treaty bodies, the analysis should be read in light of the ongoing effort to strengthen treaty bodies under the auspices of the UN High Commissioner for Human Rights and with the involvement of relevant stakeholders" -- Provided by publisher